Managerial Competence and Performance of Cimahi SMEs Mediated by Knowledge Management Effectiveness - Aam Rachmat Mulyana; Sri Hastuti; Rahardianto; Khaerul Rizal Abdurahman; R. M. Juddy Prabowo (East Asian Journal of Multidisciplinary Research, 2022)
The purpose of this study is to determine the managerial competence that affects the performance of SMEs with Knowledge Management Effectiveness as a moderating variable. There are indicators, namely Impact and Influence, Achievement Orientation, Teamwork and Cooperation, Analytical Thinking, Initiative, Developing Other, Self Confidence, Directiveness/Assertiveness, Information Seeking, Team Leadership, Conceptual Thinking and the Knowledge Management variable being the moderating variable. While the dependent variable is the performance of SMEs. The sample method used is a purposive sample with a sample size of 75 MSME owners. This study uses the Equetion Structure Equation Model with the help of SPSS v.21 and Smart PLS 3. This research method is quantitative, namely conducting a primary data search with the object of research by MSME owners registered in the trade office of SME and industrial cooperatives in the city of Cimahi. Based on the results of the partial study, the variable that has a significant effect is Knowledge Management Effectiveness, while Managerial Competence has no significant effect. Meanwhile, if Knowledge Management Effectiveness is tested as a moderating variable, then Knowledge Management Effectiveness has a moderating effect that weakens, and reduces managerial competence.